2021
DOI: 10.1007/s13304-021-01131-2
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, alcohol and drugs misuse in car and motorcycle drivers: a prevalence study in a level one trauma center

Abstract: Alcohol and drugs misuse represents an important social problem. There is no agreement about influence of ethanol and drugs on trauma severity and clinical course. The aim of this study was to investigate the impact of alcohol and drugs abuse on road related trauma managed to our Level I Trauma Center. Data of 1067 car or motorcycle drivers consecutively admitted in a 5 years period were retrospectively analyzed. The sample was divided into two groups: patients with alcohol and/or drugs misuse and patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…One study found that patients who consumed alcohol or drugs had higher severity and a greater prevalence of serious head injuries; however, there was no impact of these substances on the death of wounded patients engaged in car accidents [ 48 ]. On the contrary, our study found that there was a high probability that the patient had a positive UDS in the event of a fatal MVA, supporting the view that driving under the influence of alcohol and/or psychoactive substances increases the risk of serious, even fatal MVAs.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that patients who consumed alcohol or drugs had higher severity and a greater prevalence of serious head injuries; however, there was no impact of these substances on the death of wounded patients engaged in car accidents [ 48 ]. On the contrary, our study found that there was a high probability that the patient had a positive UDS in the event of a fatal MVA, supporting the view that driving under the influence of alcohol and/or psychoactive substances increases the risk of serious, even fatal MVAs.…”
Section: Discussionmentioning
confidence: 99%
“…Acute liver injury is defined as severe acute necrosis of hepatic cells, mostly due to liver trauma or acute liver failure, but it is also one of the most common complications of sepsis [ 1 , 2 , 3 ]. Approximately 10% of abdominal trauma involves liver parenchyma [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%